Bandgap Engineering of Bilayer Ge/CdS Thin Films via Interlayer Diffusion under Different Annealing Temperatures. (24th March 2019) - Amin, Faheem; Zahra, Syedah Afsheen; Sultan, Muhammad; Mirza, Sajjad Hussain; Azad, Fahad
Abstract : Bilayer thin films of Ge/CdS have been deposited on a glass substrate through thermal evaporation method. The obtained Ge/CdS samples were annealed at temperatures up to 400°C to observe the resulting effect on the structural changes in the film. The bandgap of the annealed films was found to increase with increasing annealing temperature which can be attributed to the increased interlayer diffusion. The interlayer diffusion was found to take effect above a temperature of 300°C which was confirmed by the Rutherford backscattering technique. Complementary XPS was done to investigate the surface stoichiometry of the bilayers.